2017
DOI: 10.1177/0020731417707491
|View full text |Cite
|
Sign up to set email alerts
|

Precarious Employment and Quality of Employment in Relation to Health and Well-being in Europe

Abstract: This article presents an overview of the recent work on precarious employment and employment quality in relation to workers' health and well-being. More specifically, the article mainly reviews the work performed in the E.U. 7th Framework project, SOPHIE. First, we present our overarching conceptual framework. Then, we provide a compiled overview of the evidence on the sociodemographic and European cross-country distribution of employment quality and employment precariousness. Subsequently, we provide the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
192
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(211 citation statements)
references
References 45 publications
6
192
0
13
Order By: Relevance
“…These findings, which are participant‐driven in nature, and validated through community member checking, clearly correspond with previous scholarship, principally using large‐scale datasets . In an overview of research on precarious employment and wellbeing in Europe, Julia et al propose general pathways through which precarious employment impacts wellbeing which are similar to our findings: adverse psychosocial experiences related to employment conditions (uncertainty about future work, discrimination, feeling powerless), material living conditions related to precariousness and exposure to poor working conditions and job content.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings, which are participant‐driven in nature, and validated through community member checking, clearly correspond with previous scholarship, principally using large‐scale datasets . In an overview of research on precarious employment and wellbeing in Europe, Julia et al propose general pathways through which precarious employment impacts wellbeing which are similar to our findings: adverse psychosocial experiences related to employment conditions (uncertainty about future work, discrimination, feeling powerless), material living conditions related to precariousness and exposure to poor working conditions and job content.…”
Section: Discussionsupporting
confidence: 90%
“…Work is a complex phenomenon that encompasses both job tasks and their attendant hazards, demands, and rewards and employment quality, which refers to contractual agreements around wages and social benefits, scheduling, and the ability for workers to have a voice regarding working conditions . Work is shaped by the intersection of macro‐ and micro‐level social, structural, and economic forces, including capitalism, systemic and individual‐level racism, sex, immigration policies, educational opportunities, and socioeconomic position .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Underemployment is related to precarity via working time arrangements and is conceptually different from broader job quality, which involves intrinsic work tasks (eg, job control, job demands) and employment conditions and relationships, (eg, terms of contracts and rewards) 30. Distinct from previous research, our paper is the first to look at the effects of both disability and underemployment on mental health.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have observed a negative association between precarious employment and workers' health outcomes, in terms of self-rated health (SRH), psychological distress, and mortality. [1][2][3][4][5][6] Similar and mostly overlapped types of employment, such as temporary, non-permanent, part-time, and more broadly atypical=non-standard employment, have also been noted to be negatively related to workers' health, [7][8][9][10][11] whereas some studies were skeptical about their negative association. 12,13 Precarious employment has become a common phenomenon in increasingly "flexible" labor markets in advanced countries over the past decades, reflecting the increased pressure on cost-cutting under global competition and labor market deregulation.…”
Section: Introductionmentioning
confidence: 99%